Studies on the life cycle and morphogenesis of Anisakis simplex (Rudolphi, 1809) (Nematoda: Anisakidae) cultured in vitro - J. Grabda (Acta Ichthyologica et Piscatoria, 1976)
In the present paper the results obtained during in vitro rearing the 3rd stage larvae of Anisakis simplex (Rud.) from Baltic herring and eggs produced by the reared females are summarised. The morphology of developmental stages obtained, i.e., the 3rd and 4th larval, adult males and females, eggs and first larval stages, is described. Different organs being formed during metamorphosis of the nematodes reared are followed.